Millennial to decadal magma evolution in an arc volcano from zircon and tephra of the 2016 Santiaguito eruption (Guatemala) - Cisneros de León, Alejandro; Schmitt, Axel Karl; Storm, Sonja; Schindlbeck, Julie Christin (Lithos, 2019)
The Santa María-Santiaguito volcanic complex collectively is one of the most active and dangerous volcanoes in the entire Central American volcanic arc. Within 20years of the destructive Plinian eruption of the Santa María stratocone (Guatemala) in 1902, the Santiaguito volcanic dome complex started to form by parasitic vent eruptions which have lasted over nearly a century. Because of the frequent eruptions of Santiaguito, it offers unique opportunities to study secular changes in its subvolcanic magma reservoir at high temporal resolution. Ash collected days and hours after eruptions of Santiaguito during an unusually explosive interval in August 2016 represents some of the least evolved compositions (60-62% SiO2) with the lowest 87Sr/86Sr isotope ratios ever reported for the system. This extends the multi-decadal trend of Santiaguito to progressively less evolved magma compositions with time, relative to the 1902 event which erupted overwhelmingly dacitic pumice. Santiaguito's geochemical changes are indicative of increasingly larger contributions of fresh basaltic andesite magma recharge mixing with dacitic magma that remained after the 1902 eruption. High-resolution secondary ion mass spectrometry (SIMS) 238U-230Th disequilibrium dating and geochemistry of zircon from Santiaguito ash and Santa María 1902 pumice reveal the presence of evolved and zircon-saturated melts over the entire ca. 100 kyr interval of basaltic andesite eruptions that constructed the Santa María central cone. Quartz diorite basement xenoliths (~55% SiO2) with Eocene zircons are common in the Santa María 1902 deposits, and a few equally old zircon xenocrysts within Santiaguito ash suggest that vestiges of assimilated Eocene crustal rocks are present in the modern magma system. Zircon crystals in andesitic Santiaguito tephra are identical in age and trace element signature to those in the 1902 pumice. This is direct evidence for the persistence of residual evolved magma with crystals dating back to the Santiaguito cone-forming stage between ca. 100 and 25ka and the pre-1902 eruptive quiescence which lasted for ca. 25 kyr. It also indicates that residual dacite still contributes to Santiaguito andesitic magmas. Zircon survival in Santiaguito andesite requires comparatively brief timescales of magma mixing between basaltic andesite and resident dacite magmas because otherwise zircon would become resorbed.